Comparative Study of Erythrocyte Sedimentation Rate (ESR) and Estrogen Level in Adolescent Women with ACNE Vulgaris in Azare Bauchi State - Ahmad Aliyu Ladan; Ahmad Aminu Muhammad; Abubakar Khalid Aliyuand; Abubakar Khadija Zirami (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Acne vulgaris is a common dermatological condition, affecting up to 85% of adolescents globally, particularly during puberty when sebaceous gland activity is heightened due to hormonal changes. Acne predominantly affects both genders but presents more severely in females, particularly during adolescence when hormonal fluctuations are most prominent. This study aimed to evaluate the hematological and biochemical indices in adolescent women with acne vulgaris. With three groups, each consisting of six participants. Group one which is a group of married women three of which are normal and three abnormal followed by group two, which is the group of unmarried adolescent women with three normal participant and three abnormal, then lastly group three for early stage of puberty within the range of 13-17 years with 3 normal and 3 abnormal also. Making the total number of 18 participants. This cross-sectional study design to assess the hematological and biochemical indices of adolescent females aged 13 to 23 years, diagnosed with acne vulgaris, from June 2024 to August 2024. Blood samples (5 mL) were collected via venipuncture and stored in EDTA tubes. Hematological indices were analyzed using an automated hematology analyzer (Sysmex KX-21N). Two biochemical indices: - Erythrocyte Sedimentation Rate (ESR) and Estrogen, were included in the analysis. The ESR values range widely from 0.5 to 88 mm/h, with a mean of 18.58. Estrogen levels also show a wide range, from 9 to 326.39 pg/ml, with a mean of 115.74. Further analysis revealed equal distribution of Ance vulgaris among the participants. This study provides valuable insights into the hematological and biochemical indices of adolescent women with acne vulgaris. The findings reveal notable variations in the hematological and biochemical parameters of the female cohorts.